2016
DOI: 10.1007/s10661-016-5549-z
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in Lagos state, Nigeria: what really changed?

Abstract: Our study revealed periodicities of 2.3 and 2.25 years in wet and dry seasons and periodicities of 2 to 5 years on seasonal and annual timescales. Minimum temperature (Tmin), maximum temperature (Tmax) and evaporation recorded increases of 2.47, 1.37 and 28.37 %, respectively, but a reduction of 19.58 % in rainfall on decadal timescale. Periodicity of 8 to 12 years was also observed in annual Tmax. Cramer's test indicated a warming trend with significant Tmax increase in February, April, July, August, October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…Lagos has a low-lying topography with slopes typically between 1-4%, and elevations ranging from or below sea level to approximately 2m above sea level [10]. The low slope angle delays the drainage of water from the land, which combined with the increase in runoff generation associated with urban expansion, increases the flood risk over time.…”
Section: Flooding In Lagosmentioning
confidence: 99%
“…Lagos has a low-lying topography with slopes typically between 1-4%, and elevations ranging from or below sea level to approximately 2m above sea level [10]. The low slope angle delays the drainage of water from the land, which combined with the increase in runoff generation associated with urban expansion, increases the flood risk over time.…”
Section: Flooding In Lagosmentioning
confidence: 99%
“…During the long rainy season, many parts of Lagos are susceptible to flooding and this is because of building of houses on flood plains, inadequate drainage of storm water, lack of maintenance of existing drainage systems, increased run-off because of uncontrolled expansions of impermeable surfaces and weak institutional capacity (Adelekan 2010). Lagos State ranks 15th in the world in terms of population exposed to coastal flooding (Sojobi, Balogun & Salami 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Streams of river basins with smaller drainage area are known to respond quickly to climate change on shorter timescales ranging from hours to days to months (Chen et al 2010). Located close to the Atlantic Ocean is a small deltaic drainage area; this makes the rivers and streams in Lagos State very sensitive to the extreme rainfall resulting from climate change and the impact of human activity (Sojobi et al 2015). Also the frequency of storm surges may be exacerbated by sea level rise, especially at high tides and during the rainy season, characterised by heavy rainfall of long duration and intensity and increasing inadequacy of drainage systems (Adelekan 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia has a total of fourteen prototype school building designs, in total there are 14 designs. Any fault in the design will be replicated many times, in a study conducted by Sojobi et al [1], which investigate the climate change in Lagos state, Nigeria. Various studies have demonstrated the importance of climate and microclimatic studies and their influencing factors, variabilities and interactions Sojobi et al [1]; Deng et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…Any fault in the design will be replicated many times, in a study conducted by Sojobi et al [1], which investigate the climate change in Lagos state, Nigeria. Various studies have demonstrated the importance of climate and microclimatic studies and their influencing factors, variabilities and interactions Sojobi et al [1]; Deng et al [2]. The study indicated that the persistent state of minimum temperature often precedes the arrival and reversal of the phase of the maximum temperature.…”
Section: Introductionmentioning
confidence: 99%